2009
DOI: 10.1093/alcalc/agn114
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hair Pigment on the Incorporation of Fatty Acid Ethyl Esters (FAEE)

Abstract: FAEE incorporation into hair does not appear to be affected by hair pigment, which is in congruence with what is known about the chemistry of drug-melanin interactions. This is important in avoiding potential bias and discrimination in the interpretation of alcohol abuse based on hair color.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…The use of specific diagnostic biomarkers for chronic alcohol consumption, ethyl glucuronide (EtG) and fatty acid ethyl esters (FAEEs), has been investigated in various matrices including hair. 45,62,145 EtG and FAEEs are affected by cosmetic treatments; however, their incorporation into hair is not affected by hair pigmentation. 45,156 The SoHT published a consensus statement in 2009 recommending identification of either EtG or FAEEs in hair for assessing chronic alcohol consumption while encouraging identification of both.…”
Section: Chronic Excessive Alcohol Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of specific diagnostic biomarkers for chronic alcohol consumption, ethyl glucuronide (EtG) and fatty acid ethyl esters (FAEEs), has been investigated in various matrices including hair. 45,62,145 EtG and FAEEs are affected by cosmetic treatments; however, their incorporation into hair is not affected by hair pigmentation. 45,156 The SoHT published a consensus statement in 2009 recommending identification of either EtG or FAEEs in hair for assessing chronic alcohol consumption while encouraging identification of both.…”
Section: Chronic Excessive Alcohol Consumptionmentioning
confidence: 99%
“…45,62,145 EtG and FAEEs are affected by cosmetic treatments; however, their incorporation into hair is not affected by hair pigmentation. 45,156 The SoHT published a consensus statement in 2009 recommending identification of either EtG or FAEEs in hair for assessing chronic alcohol consumption while encouraging identification of both. 5 Recommendations are given with respect to analytical instrumentation, GC or LC tandem MS for EtG and headspace solid-phase microextraction with GC-MS for FAEEs and the cut-offs to employ, as listed in Table 5.…”
Section: Chronic Excessive Alcohol Consumptionmentioning
confidence: 99%
“…In order to test the hypothesis that FAEE do not preferentially accumulate in pigmented hair, the Motherisk laboratory developed an experimental model using Long Evans rats; rats that contain naturally occurring black and white patches of hair. Results show that FAEE are detectable in this model post-treatment with ethanol, and that there is no statistical difference in levels of cumulative FAEE between white and black hair, respectively [42]. Therefore, these results indicate the FAEE hair test is not likely susceptible to a hair colour bias.…”
Section: Hair Faee Using Animal Modelsmentioning
confidence: 57%
“…It was shown that false positive results may originate from frequent treatment with ethanol containing hair lotions [11,12]. No effect of pigmentation on FAEE concentration in hair was found [13].…”
Section: Introductionmentioning
confidence: 99%